2012
DOI: 10.1002/ajmg.a.35235
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental features in 2q23.1 microdeletion syndrome: Report of a new patient with intractable seizures and review of literature

Abstract: 2q23.1 microdeletion syndrome is a recently characterized chromosomal aberration disorder uncovered through array comparative genomic hybridization (array CGH). Although the cardinal feature is intellectual disability (ID), neurodevelopmental features of the syndrome have not been systematically reviewed. We present a 5-year-old boy with severe psychomotor developmental delay/ID, progressive microcephaly with brain atrophy, growth retardation, and several external anomalies. He manifested intractable epilepsy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
3
8
0
1
Order By: Relevance
“…16,17 It has been suggested that 2q23.1 deletions could be deletion mediated by recently delineated genomic rearrangement mechanism Fork Stalling and Template Switching (FoSTeS)/microhomologymediated break-induced replication (MMBIR). 9 Upon aligning the 65 deletion regions, the study found that the smallest region of overlap (SRO) was defined to one gene, MBD5. 2 Single asterisks indicate cases known to be de novo.…”
Section: Other Behaviorsmentioning
confidence: 99%
“…16,17 It has been suggested that 2q23.1 deletions could be deletion mediated by recently delineated genomic rearrangement mechanism Fork Stalling and Template Switching (FoSTeS)/microhomologymediated break-induced replication (MMBIR). 9 Upon aligning the 65 deletion regions, the study found that the smallest region of overlap (SRO) was defined to one gene, MBD5. 2 Single asterisks indicate cases known to be de novo.…”
Section: Other Behaviorsmentioning
confidence: 99%
“…A multi-institution collaboration of clinical diagnostic laboratories resulted in inclusion of additional patients not previously published from the Greenwood Genetic Center (Cases 9–12), Pathology Associates Medical Laboratories (Cases 13–14), Virginia Commonwealth University (Case 15), Fullerton Genetics Center (Case 16), and Boston Children’s Hospital (Case 17) that were identified with different cytogenomic microarray platforms. Phenotypes were further considered in the analysis of two MBD5 deletion cases reported by Motobayashi et al 19 (Motobayashi/Case 18) and Noh et al 20 (Noh/Case 19) as well an intragenic frameshift mutation c.150del or p.Thr52Hisfs*31 described by Kleefstra et al 5 (Kleefstra/Case 20) and an intragenic indel of -TC at position 148,942,435 in hg18 of exon 9 described by O’Roak et al 21 (O’Roak/Case 21), all of which were published after the Talkowski et al study 6 . The final patient, DGAP235 (Case 22), was enrolled in the Developmental Genome Anatomy Project (DGAP; www.dgap/harvard.edu) based on karyotypic detection of a de novo , balanced translocation 46,XY,t(2;5)(q22;q22), which was found to disrupt MBD5 by massively parallel paired-end sequencing; this case was independent of two previously published translocations targeting MBD5 .…”
Section: Methodsmentioning
confidence: 99%
“…ASD: autism spectrum disorders; ID/DD: intellectual disability/developmental delay; SCZ: schizophrenia; ADHD: attention deficit/hyperactivity disorder. Del: deletion; Dup: duplication [Vrijenhoek et al, ; Helbig et al, ; Niklasson et al, ; Shinawi et al, ; de Kovel et al, ; Cooper et al, ; Levinson et al, ; Lionel et al, ; Philip and Bassett, ; Sanders et al, ; Talkowski et al, ; Crespi and Crofts, ; Malhotra and Sebat, ; Motobayashi et al, ; Schaaf et al, ; Williams et al, ; Bena et al, ; Girirajan et al, ; Moller et al, ; Vorstman et al, ].…”
Section: Molecular Genetics and Diagnostic Boundariesmentioning
confidence: 99%